An effective strategy to enhance mechanical, electrical, and electromagnetic shielding effectiveness of chlorinated polyethylene-carbon nanofiber nanocomposites. (15th January 2017) - Mondal, Subhadip; Nayak, Lalatendu; Rahaman, Mostafizur; Aldalbahi, Ali; Chaki, Tapan K.; Khastgir, Dipak; Das, Narayan Ch
Abstract: Chlorinated polyethylene (CPE) filled with functionalized heat treated carbon nanofiber (CNF) nanocomposites were prepared using two different techniques like melt mixing and solution cum melt mixing. A better dispersion of CNFs in nanocomposite was achieved by solution cum melt mixing compared to only melt mixing process. The effect of mechanical, electrical conductivity ( σ), and electromagnetic interference shielding effectiveness (EMI SE) were studied. Nanocomposites prepared by solution cum melt mixing process showed higher mechanical properties, electrical conductivity ( σ ), and electromagnetic interference shielding effectiveness (EMI SE) compared to that of melt mixing process. 1 wt% CNFs filled nanocomposites prepared by the solution followed by melt mixing showed 124% higher tensile strength whereas at the same percentage of CNFs, melt processed nanocomposite exhibited 58% higher in tensile strength compared to neat CPE. The EMI SE and σ of both types of nanocomposites were increased with increasing CNFs loading. At 10 wt% CNFs loading, solution cum melt processed nanocomposite showed EMI SE 24 dB; whereas at the same wt% of CNFs loading, melt processed nanocomposite showed 22 dB. Thermogravimetric analysis was carried to investigate the thermal stability of CPE/CNF nanocomposites.